Putting Folklore To Use - Jones, Michael Owen (Book collections on Project MUSE., 1994)
Essays by thirteen folklorists explore applications in such areas as museums, aiding the homeless, environmental planning, art therapy, designing public spaces, organizing development, tourism, the public sector, aging, and creating an occupation's image.""